Urban development impacts on soil health and function: a landscape architecture perspective from the Flint Hills Ecoregion. - Freeman, Kiona Marie (Kansas State University, 2023)
Urban development is increasing worldwide, resulting in a decrease in healthy soil and leading to a loss in associated ecosystem functions. Understanding the impacts of urban development on ecosystem functioning and soil health is vital because healthy soil is essential for biosphere health. Landscape architecture relies heavily on healthy, high-functioning soil for the success of project work and the management of greenspaces to provide vital ecosystem services. Landscape architects are uniquely positioned to transform the landscape, prevent or restore degraded urban spaces, and promote well-functioning greenspace in urban areas, thus improving the ecological and social quality of urban spaces. Understanding the components of soil and how their attributes and interactions affect soil functions is essential to the profession. Understanding the impact of development on soil can help prevent land degradation due to careless design practices. This research sought to understand the effects of urban development and disturbance on soil and assess the potential for urban landscapes to provide similar soil health and function as native grasslands. This research informs readers of the importance of soil health and functions in creating living soils and healthy landscapes. By assessing sites under different land use and management practice in and around Manhattan, Kansas, USA, we researcher evaluated the impact of urban development on soil health using microbial function as the primary indicator. Recent urban development impacted soil nutrient pools influencing microbial function; however, landscape management influenced the range of those impacts. Understanding the implications of soil quality loss via management, urban disturbance, and other interventions should be of interest to landscape architects as these impacts diminish the health of the land and associated flora, fauna, and aquatic resources. Soil health influences the health of human communities and the sustainability and ecological function of the earth and its ecosystems.
Keywords: Soil health; Soil carbon; Urban development; Microbial function